Adsorption of bisphenol A from aqueous solutions by Pleurotus eryngii immobilized on Amberlite XAD-4 using as a new adsorbent. Issue 47 (7th October 2016) - Yonten, Vahap; Ince, Muharrem; Tanyol, Mehtap; Yildirim, Numan
Abstract: The adsorption of bisphenol A (BPA) in a fixed-bed column was evaluated in this work. Fungus Pleurotus eryngii isolated from Tunceli (Turkey) immobilized on XAD-4 resin was used as an adsorbent for decontamination of BPA from aqueous solutions. The extent of BPA removal capacity was evaluated as a function of parameters such as pH, volume of the sample, and column bed height. Adsorption isotherms of BPA on immobilized P. eryngii were determined and correlated with common isotherm equations such as Langmuir and Freundlich models. The mechanism of adsorption of BPA was analyzed preadsorption (XAD-4 + fungus) and postadsorption (XAD-4 + fungus + BPA) using fourier transform infrared spectroscopy. The results show that adsorption ability of BPA by immobilized P. eryngii is possible and this system yields the best degree of BPA removal (90%) at pH 11 for an initial load of 120 mg L −1 . Therefore, this material can be used as a very effective adsorbent for BPA decontamination in aqueous solutions.